MODEL PEMBELAJARAN AIR (AUDITORY INTELLECTUALLY AND REPETITION ) MELALUI MULTIMEDIA INTERAKTIF BERBASIS ARCADE GAME - Rahmanda, Kusdear (2017)
This research aims to designing and develop interactive multimedia-based on arcade game, subject of this research is the students of Vocational High School (VHS) class X (ten) at Bandung city as well as determine the increase in material students understanding the concept of network technologies and network topologies. The method used in this study is a mixed method using strategies embedded / nested concurrent, consisting of qualitative research methods (secondary) and quantitative research methods (primary). Qualitative research methods occur during the development of multimedia-based learning carried out arcade game. To determine the quality of the developed multimedia testing by media experts and subject experts using a questionnaire developed by Learning Object Review Instrument (LORI) version 1.5. From the test results obtained by media expert ratings of 85.34% is included into either category and assessment by subject experts of 84% is included in both categories. Based on the two values obtained can be concluded that the multimedia-based arcade game is decent for use in learning. Meanwhile, the method of quantitative research carried out at the time of data analysis increased the understanding of learners after experiencing learning using multimedia. The data obtained from the pretest and posttest given to students or classes that have been given learning using AIR (Auditory intellectually repetition) learning model through interactive multimedia-based arcade game. The average value of pretest obtained at 10.41, while the average value posttest was 14.41. From both the average value can be obtained gain value of 0.42 which showed an increased understanding of the learners.;---Penelitian ini bertujuan untuk merancang dan membangun multimedia interaktif berbasis arcade game, Subjek dari penelitian ini adalah peserta didik Sekolah Menengah Kejuruan (SMK) kelas X (sepuluh) di kota Bandung serta mengetahui peningkatan pemahaman peserta didik dalam materi konsep teknologi jaringan dan topologi jaringan. Metode penelitian yang digunakan pada penelitian ini adalah mixed method dengan menggunakan strategi embedded/nested konkuren, terdiri dari metode penelitian kualitatif (sekunder) dan metode penelitian kuantitatif (primer). Metode penelitian kualitatif terjadi pada saat pengembangan multimedia pembelajaran berbasis arcade game dilakukan. Untuk mengetahui kualitas dari multimedia yang dikembangkan dilakukan pengujian oleh ahli media dan ahli materi menggunakan kuesioner yang dikembangkan berdasarkan Learning Object Review Instrument (LORI) versi 1.5. Dari pengujian tersebut diperoleh hasil penilaian oleh ahli media sebesar 85,34% yang termasuk ke dalam kategori baik dan penilaian oleh ahli materi sebesar 84% yang termasuk ke dalam kategori baik. Berdasarkan dua nilai yang diperoleh dapat disimpulkan bahwa multimedia pembelajaran berbasis arcade game ini layak untuk digunakan dalam pembelajaran. Sementara itu, metode penelitian kuantitatif dilakukan pada saat menganalisa data peningkatan pemahaman peserta didik setelah mengalami pembelajaran menggunakan multimedia. Data tersebut diperoleh dari hasil pretest dan posttest yang diberikan kepada peserta didik atau kelas yang telah diberikan pembelajaran menggunakan model pembelajaran AIR ( Auditory Intellectually and Repetition ) melalui multimedia interaktif berbasis arcade game. Nilai rata-rata pretest yang diperoleh sebesar 10,41, sedangkan nilai rata-rata posttest sebesar 14,41. Dari kedua nilai rata-rata tersebut dapat diperoleh nilai gain sebesar 0,42 yang menunjukkan adanya peningkatan pemahaman peserta didik.